A comparison of two methods of assessing orthodontic treatment need in the mixed dentition: DAI and IOTN - Johnson Mark; Harkness Michael; Crowther Paul; Herbison Peter (Sciendo, 2000)
This paper assesses the unmet orthodontic treatment need in a random sample of 10-year-old schoolchildren, using two indices: the Dental Aesthetic Index (DAI) and the Index of Orthodontic Treatment Need (IOTN). The DAI scores were adjusted by omitting the missing teeth component of the index because many children were in the mixed dentition with unerupted permanent teeth. Although both indices assessed the same number of children with malocclusions requiring orthodontic treatment, not all were ranked similarly by each index.